2019
DOI: 10.1002/app.47449
|View full text |Cite
|
Sign up to set email alerts
|

Silica nanoparticles reinforced natural rubber latex composites: The effects of silica dimension and polydispersity on performance

Abstract: The nano‐size autonomous monodisperse silica (AS) particles were prepared by hydrolysis and condensation of tetraethoxysilane using l‐lysine as catalyst. The silica/natural rubber (NR) masterbatches were then produced via latex compounding, in which NR latex was mixed with the above AS dispersion. The commercial precipitated silica (PS) was introduced as a control. The effects of both AS and PS particles on the interfacial and mechanical properties of composites were systematically examined. It was found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…5,6 Silica nanoparticles with surface modication are of great interest as potential supports for proteins, 7 therapeutic drugs, [8][9][10][11] uorophores, 12,13 active groups for separation/catalysis, [14][15][16][17][18][19] and polymers. 13,[20][21][22] Surface modication also allows redispersion and colloidal stability in a variety of media, [23][24][25] which has been difficult specically for silica due to the high density of surface silanol groups causing irreversible aggregation. 26 It has been reported that irreversible aggregation becomes more severe as particle sizes decrease, 24,27 but in the case of mesoporous particles complete redispersion can be obtained aer drying with the aid of sonication, with the smallest hydrodynamic diameter obtained approximately 40 nm.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Silica nanoparticles with surface modication are of great interest as potential supports for proteins, 7 therapeutic drugs, [8][9][10][11] uorophores, 12,13 active groups for separation/catalysis, [14][15][16][17][18][19] and polymers. 13,[20][21][22] Surface modication also allows redispersion and colloidal stability in a variety of media, [23][24][25] which has been difficult specically for silica due to the high density of surface silanol groups causing irreversible aggregation. 26 It has been reported that irreversible aggregation becomes more severe as particle sizes decrease, 24,27 but in the case of mesoporous particles complete redispersion can be obtained aer drying with the aid of sonication, with the smallest hydrodynamic diameter obtained approximately 40 nm.…”
Section: Introductionmentioning
confidence: 99%
“… [ 20 ] Silica -precipitated silica (PS), autonomous monodisperse silica (AS) Silane treatment Silica dimension and polydispersity Tensile Strength and Abrasive Resistance PS reinforced rubber showed better tensile strength and abrasive resistance than AS reinforced rubber. [ 21 ] Silica from rice husk Alkali treatment Silica loading of 60 phr Curing Characteristic The result shows that the curing time of the rubber composites decrease with increasing silica loading. Tensile Strength The tensile strength was determined at the break point of the specimen.…”
Section: Conventional Fillers For Natural Rubber Nanocompositementioning
confidence: 99%
“…12,13 Consequently, unmodified silica can easily aggregate into larger-sized particles in rubber matrix through the interaction between silanols, and cause poor reinforcement effect. 14,15 The surface modification of silica is a very effective route to prevent the aggregation of silica particles, and silane-coupling agents are widely used to modify surface of inorganic particles. The silanols formed by hydrolysis of silane-coupling agent can dehydrate and condense with the silanols on the surface of silica to form silyl ether, which is chemically bonded to the surface of silica to prevent the formation of silica aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…However, with a large number of polar silanols on the surface, silica exhibits strong hydrophilicity and poor compatibility with most hydrophobic rubber matrices 12,13 . Consequently, unmodified silica can easily aggregate into larger‐sized particles in rubber matrix through the interaction between silanols, and cause poor reinforcement effect 14,15 …”
Section: Introductionmentioning
confidence: 99%